Polyhydroxyalkanoates are essential for maintenance of redox state in the Antarctic bacterium Pseudomonas sp. 14-3 during low-temperature adaptation - Ayub, Nicolás Daniel; Tribelli, Paula Maria; López, Nancy Irene (Extremophiles)
Polyhydroxyalkanoates (PHAs) are highly reduced bacterial storage compounds that increase fitness in changing environments. We have previously shown that phaRBAC genes from the Antarctic bacterium Pseudomonas sp. 14-3 are located in a genomic island containing other genes probably related with its adaptability to cold environments. In this paper, Pseudomonas sp. 14-3 and its PHA synthase-minus mutant (phaC) were used to asses the effect of PHA accumulation on the adaptability to cold conditions. The phaC mutant was unable to grow at 10°C and was more susceptible to freezing than its parent strain. PHA was necessary for the development of the oxidative stress response induced by cold treatment. Addition of reduced compounds cystine and gluthathione suppressed the cold sensitive phenotype of the phaC mutant. Cold shock produced very rapid degradation of PHA in the wild type strain. The NADH/NAD ratio and NADPH content, estimated by diamide sensitivity, decreased strongly in the mutant after cold shock while only minor changes were observed in the wild type. Accordingly, the level of lipid peroxidation in the mutant strain was 25-fold higher after temperature downshift. We propose that PHA metabolism modulates the availability of reducing equivalents, contributing to alleviate the oxidative stress produced by low temperature. © 2008 Springer. Fil: Ayub, Nicolás Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: Tribelli, Paula Maria. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: López, Nancy Irene. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina